2006
DOI: 10.1258/135581906778476544
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of evidence about extended roles for allied health professionals

Abstract: A range of extended practice roles for allied health professionals have been promoted and are being undertaken, but their health outcomes have rarely been evaluated. There is also little evidence as to how best to introduce such roles, or how best to educate, support and mentor these practitioners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
130
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(136 citation statements)
references
References 33 publications
1
130
0
5
Order By: Relevance
“…plain film reporting) as means of increasing (reporting) capacity [159,160]. A previous review [15] of the evidence on the effectiveness of ESP concluded that most of the studies explored the acceptance of these roles by other professional colleagues; however, their impacts on services were not evaluated. We found three ESP studies, all performed within the NHS, UK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…plain film reporting) as means of increasing (reporting) capacity [159,160]. A previous review [15] of the evidence on the effectiveness of ESP concluded that most of the studies explored the acceptance of these roles by other professional colleagues; however, their impacts on services were not evaluated. We found three ESP studies, all performed within the NHS, UK.…”
Section: Discussionmentioning
confidence: 99%
“…Pooling of results in a metaanalysis is inappropriate for the current review due to a high level of heterogeneity. The narrative synthesis is widely used in this situation [15,16]. Therefore, we present a narrative synthesis of our findings.…”
Section: Data Synthesismentioning
confidence: 97%
“…Positive outcomes of these expanded roles include improved wait times for surgery, decreased health care costs, earlier diagnoses, fewer duplicate referrals, and increased patient satisfaction. [5][6][7][8][9][10][11][12] Physiotherapists practising beyond their regulated entry-level scope of practice-that is, those who have undertaken formal continuing education programs to gain additional knowledge and skills that are formally recognized 13 -are known as advanced practitioners in Canada, Australia, and New Zealand; the United States and the United Kingdom use the terms extended scope physiotherapist or consultant. 14 In this article, we use advanced practitioners to describe physiotherapists practising in this capacity.…”
mentioning
confidence: 99%
“…Extended scope physiotherapists (ESPs) work within a range of services crossing established boundaries of practice between medicine, nursing and allied health professionals (Gardiner and Turner, 2002;McPherson et al 2006). Enhancing pathways to appropriate management has been a key UK government directive (DOH, 2006;2013) and in response many services have looked at innovative ways to deliver care, such as providing extended roles, which in turn has fuelled the growth of ESP practice.…”
Section: Study Contextmentioning
confidence: 99%